KONSTRUKSI SOSIAL BUDAYA MAPALUS DI KELOMPOK TANI MAHKARIA KELURAHAN TARATARA SATU KECAMATAN TOMOHON BARAT KOTA TOMOHON (The Socio-cultural Construction of Mapalus in the Mahkaria Farmer Group in Taratara Satu Village, Tomohon Barat District, Tomohon City) - Veila Sendi Motto; Benu Olfie L.S,; Charles R. Ngangi (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
This study aimed to describe the socio-cultural construction of mapalus in the Mahkaria farmer group in Taratara Satu Village, Tomohon Barat District, Tomohon City. This research was conducted in February-September 2019. Types of data used in this study were primary and secondary data. Secondary data were obtained from the Tomohon City Statistics Office, while primary data were obtained directly from respondents. The measured variables were the type of mapalus activity that was followed, membership, implementation, and response. The results showed that the existing mapalus culture was still preserved, maintained and well cared through the construction of each group member, especially in the agricultural mapalus field.Keywords: Construction, Socio-Culture, Mapalus